The jukebox man - Ogburn, Jacqueline K.; Ransome, James (New York : Dial Books for Young Readers, 1998)
After watching her grandfather repair broken jukeboxes and change records at diners, restaurants, fish camps, and truck stops, a little girl dances with him to her favorite tune.
School Library Journal
Christian Library
2.8
K-3
Keywords: Grandfathers -- Fiction; Jukeboxes -- Fiction; Grandparent and child -- Fiction; Grandfathers -- Fiction; Jukeboxes -- Fiction; Grandparent and child -- Fiction